Theoretical and legal aspects of syllabus design - Varych, O.; Savokhina, M. (Problems of Engineer-Pedagogical Education, 2021)
The paper considered the theoretical and legal aspects of syllabus design as an alternative form of the curriculum of a specific educational component of the educational program. The subject of the study is syllabus projects, as well as legal norms of legislation in the field of education. A detailed analysis of the legislator's position on the inconsistency in certain provisions of regulations in the framework of unambiguous use of the terms "discipline" and "educational component" was made. The unified model of a syllabus taking into account degree of academic freedom of the teacher at formation of its separate elements was offered. Depending on the degree of the syllabus components normativeness, the authors proposed to distinguish normative, relatively normative and creative elements of the syllabus. The requirements for the formation of curricula on the basis of which the syllabus is formed are analyzed in detail, the procedure for reflecting the learning outcomes enshrined in educational programs is proposed and possible formalized ways of confirming these learning outcomes by students are possible. An analysis of the recommendations of the University of Washington and Stanford University on the development of syllabuses were made. On the basis of these resources, parallels were drawn with the possible transformation of the proposed components into local regulations of Ukrainian higher education institutions, their compliance with the realities of modern Ukrainian higher education. The normative components of syllabus and the difference of approaches to their formation in domestic free economic zones were studied in the most detail. The provisions of legislative acts, which stipulate the obligation to have some elements of the syllabus, as well as the possible variable behavior of higher education institutions in the process of formalizing the practice of creating syllabuses in local regulations, were studied. The authors reviewed the Regulations of higher education institutions that regulate the process of syllabus development in order to comply with the requirements set out in them to regulations in the field of education and to identify the universal components of syllabus. The authors also considered the transformation of the principle of student-centered learning and academic integrity into a new normative document.